2018
DOI: 10.3168/jds.2017-13944
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: In vitro rumen gas production and starch degradation of starch-based feeds depend on mean particle size

Abstract: Our objective was to model the effect of mean particle size (mPS) on in vitro rumen starch degradation (IVSD) and the kinetics of gas production for different starch-based feeds. For each feed, 2 batches of the same grains were separately processed through 2 different mills (cutter or rotor speed mills), with or without different screens to achieve a wide range of mPS (0.32 to 3.31 mm for corn meals; 0.19 to 2.81 mm for barley meals; 0.16 to 2.13 mm for wheat meals; 0.28 to 2.32 mm for oat meals; 0.21 to 2.36 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…Another factor that can influence the rate of gas production is the type of substrate digested. Moreover, Gallo et al (2018) revealed that the particle size of the substrate influenced the rate of gas production.…”
Section: Discussionmentioning
confidence: 99%
“…Another factor that can influence the rate of gas production is the type of substrate digested. Moreover, Gallo et al (2018) revealed that the particle size of the substrate influenced the rate of gas production.…”
Section: Discussionmentioning
confidence: 99%
“…Pulverization and granulation increase the contact area between dietary fiber and rumen microorganisms and promotes the degradation of dietary fiber. Studies have shown a linear decrease in the degradation rate occurs with increases in the average particle sizes of barley, wheat, rye, and pea flour [9]. Therefore, the effective degradation rate in the rumen of low concentrate diet was not much worse than that of the high concentrate diet.…”
Section: Effect Of Pyruvate Infusion On Ruminal A: P Ratiomentioning
confidence: 96%
“…El haba (Vicia faba L.) es una leguminosa anual originaria del Mediterráneo con distribución mundial, que se caracteriza por ser capaz de crecer en diferentes zonas climáticas (Nieto-Sierra et al, 2020), desarrollar un follaje abundante, tener un alto contenido proteico, alta digestibilidad, ser rica en carbohidratos solubles (Gallo et al, 2018;Johnston et al, 2019).…”
Section: Materiales Y Métodosunclassified